BSL-4 for High Risk Animal Pathogens in India - Kulkarni, Diwakar D (Indian Farming, 2015)
Due to the long untiring efforts of some visionaries, the BSL-4 Biocontainment Lab was established in Bhopal, the first of its kind in India to work on exotic diseases of animals.